The winged : an upper Missouri River ethno-ornithology - Chandler, Kaitlyn; James, Robert (Robert B.); Clements, Samrat; Zedeño, María Nieves; Field Murray, Wendi (Anthropological papers of the University of Arizona, 2017)
"Investigates social interactions between Native American groups and birds along the upper Missouri River in all their tangible and intangible expressions"--Provided by publisher.